Nivel de asociatividad del sector emprendedor de la economía popular y solidaria, cantón Machala. - Santana Ochoa, Karen Yamileth (My University, 2020)
In order to improve the functioning of the organizations of the popular and solidary economy of the Machala canton, it is proposed to determine their level of associativity and discuss some forms of incentive for their members. Then, an estimated weighting of each characteristic of this informal business sector is achieved. With this purpose, a series of indicators are proposed that allow organizations to be classified according to their characteristics, management model and contribution to economic and social development. Established the fundamental parameters of the entrepreneurial sector of the popular and solidarity economy, those intervals that are applicable to compare the degree of association of the different organizations of the Machala canton are estimated. It is established that decision-making is the main indicator of solidarity association, followed by factors of production and the distribution of surpluses. The relative low associativity of the popular and solidarity economy organizations of the Machala canton makes it urgently necessary to promote training, inclusion and accompaniment policies.
Para mejorar el funcionamiento de las organizaciones de la economía popular y solidaria del cantón Machala, se propone determinar su nivel de asociatividad y discutir sobre algunas formas de incentivo a sus integrantes. En este sentido, se logra hacer una ponderación estimada de cada una de las características de ese sector informal empresario. Para esto, se plantean una serie de indicadores que permiten clasificar a las organizaciones de acuerdo con sus características, modelo de gestión y contribución al desarrollo económico y social. Establecidos los parámetros fundamentales del sector emprendedor de la economía popular y solidaria, se estiman aquellos intervalos que sean aplicables para comparar el grado de asociación de las diferentes organizaciones del cantón Machala. Se establece que la toma de decisiones es el principal indicador de asociatividad solidaria, seguido de los factores de producción y la repartición de excedentes. La relativa poca asociatividad de las organizaciones de economía popular y solidaria del cantón Machala hace latente la necesidad de fomentar políticas de capacitación, inclusión y acompañamiento.
Keywords: ECONOMÍA COLECTIVA; EMPRESARIO; ASOCIACIÓN; SECTOR INFORMAL